Is There a Role for Basophils in Cancer? - Marone, Giancarlo; Schroeder, John T.; Mattei, Fabrizio; Loffredo, Stefania; Gambardella, Adriana Rosa; Poto, Remo; de Paulis, Amato; Schiavoni, Giovanna; Varricchi, Gilda (Frontiers in Immunology, 2020)
Basophils were identified in human peripheral blood by Paul Ehrlich over 140 years ago. Human basophils represent less than 1% of peripheral blood leukocytes. During the last decades, basophils have been described also in mice, guinea pigs, rabbits, and monkeys. There are many similarities, but also several immunological differences between human and mouse basophils. There are currently several strains of mice with profound constitutive or inducible basophil deficiency useful to prove that these cells have specific roles in vivo. However, none of these mice are solely and completely devoid of all basophils. Therefore, the relevance of these findings to humans remains to be established. It has been known for some time that basophils have the propensity to migrate into the site of inflammation. Recent observations indicate that tissue resident basophils contribute to lung development and locally promote M2 polarization of macrophages. Moreover, there is increasing evidence that lung-resident basophils exhibit a specific phenotype, different from circulating basophils. Activated human and mouse basophils synthesize restricted and distinct profiles of cytokines. Human basophils produce several canonical (e.g., VEGFs, angiopoietin 1) and non-canonical (i.e., cysteinyl leukotriene C4) angiogenic factors. Activated human and mouse basophils release extracellular DNA traps that may have multiple effects in cancer. Hyperresponsiveness of basophils has been demonstrated in patients with JAK2V617F-positive polycythemia vera. Basophils are present in the immune landscape of human lung adenocarcinoma and pancreatic cancer and can promote inflammation-driven skin tumor growth. The few studies conducted thus far using different models of basophil-deficient mice have provided informative results on the roles of these cells in tumorigenesis. Much more remains to be discovered before we unravel the hitherto mysterious roles of basophils in human and experimental cancers.